Tri-2-Hydroxyarachidonein Induces Cytocidal Autophagy in Pancreatic Ductal Adenocarcinoma Cancer Cell Models - Fernández-Díaz, Javier; Beteta-Göbel, Roberto; Torres, Manuel; Cabot, Joan; Fernández-García, Paula; Lladó, Victoria; Escribá, Pablo V.; Busquets, Xavier (Frontiers in Physiology, 2022)
Cell proliferation in pancreatic cancer is determined by a complex network of signaling pathways. Despite the extensive understanding of these protein-mediated signaling processes there are no significant drug discoveries that could considerably improve patient survival. However, the recent understanding of lipid-mediated signaling gives a new prespective on the control of the physiological state of pancreatic cells. Lipid signaling plays a major role in the induction of cytocidal autophagy and can be exploited by using synthetic lipids to induce cell death in pancreatic cancer cells. In this work, we studied the activity of a synthetic lipid, tri-2-hydroxyarachidonein (TGM4), which is a triacylglycerol mimetic that contains 3 acyl moieties with 4 double bonds each, on cellular and in vivo models of pancreatic cancer. We demonstrated that TGM4 inhibited proliferation of Mia-PaCa-2 (human pancreatic carcinoma) and PANC-1 (human pancreatic carcinoma of ductal cells) in in vitro models and in an in vivo xenograft model of Mia-PaCa-2 cells. In vitro studies demonstrated that TGM4 induced cell growth inhibition paralleled with an increased expression of PARP and CHOP proteins together with the presence of sub-G0 cell cycle events, indicating cell death. This cytocidal effect was associated with elevated ER stress/autophagy markers such as BIP, LC3B and DHFR. In addition, TGM4 activated PPAR-γ, induced elevated levels of p-AKT and down-regulation of p-c-Jun. We conclude that TGM4 induced pancreatic cell death by activation of cytocidal autophagy. This work highlights the importance of lipid signaling in cancer and the use of synthetic lipid structures as novel and potential approaches to treat pancreatic cancer and other neoplasias.